Gamer teachers - Gibson, David; Halverson, B.; Riedel, E. (Information Sciene Publishing, 2007)
The divergence between the generation of people who grew up before versus after computer games became ubiquitous – a new kind of digital divide - is characterized by differences in thinking patterns, perceptions about the world, approaches to challenges, evaluation of risks, and expectations about leading and interacting with other people. Some argue that because of these sorts of differences, students of today have new expectations about learning, which suggests that we need new approaches to teaching and gamer teachers (the pun is intended). This chapter outlines a potential framework for research on teaching that understands and uses the power of computer games and simulations to improve student achievement. Along the way, we raise new research questions, which we hope that you and others will help answerThe divergence between the generation of people who grew up before versus after computer games became ubiquitous – a new kind of digital divide - is characterized by differences in thinking patterns, perceptions about the world, approaches to challenges, evaluation of risks, and expectations about leading and interacting with other people. Some argue that because of these sorts of differences, students of today have new expectations about learning, which suggests that we need new approaches to teaching and gamer teachers (the pun is intended). This chapter outlines a potential framework for research on teaching that understands and uses the power of computer games and simulations to improve student achievement. Along the way, we raise new research questions, which we hope that you and others will help answer.